Work and Identity - Mółka, Janusz (Horyzonty Wychowania, 2015)
A few years ago “Horizons of Education” [2/2003 (4)] publishedan issue under the characteristic title Anxiety over Identity.The subject matter concerned the attempts to look at the issueof identity with reference to human nature, culture, religion, ethics,psychology, pedagogy. It was observed that human identityis something dynamic and it cannot be defined once and for all.On the contrary, it requires constant clarifying and defining theanswer to the question: Who is man? What is his place in the surrounding world? What is his relation to other people? It is worthnoticing that contemporary interpretations of identity attempt toexplain the processes of searching for and achieving human identity with the help of such concepts as history of development, the conception of oneself, social rights, identity of social roles, social identity, personal identity. One can thus state that the notion of identity is a key concept in anthropology based on psychology, sociology, or pedagogy. The following issue is intended to look at discovering and experiencing human identity from the perspective of work. We are aware that through work people fulfil themselves...